1996
DOI: 10.1172/jci118970
|View full text |Cite
|
Sign up to set email alerts
|

Acute lung injury fibroblast migration and invasion of a fibrin matrix is mediated by CD44.

Abstract: Fibrosis results when myofibroblasts invade the wound fibrin provisional matrix. Extracellular matrix receptors on the cell surface mediate cell adhesion, migration, and invasion. Recent work with transformed cells indicates that these cells use the cell surface matrix receptor CD44 for migration and invasion. In this study, we examine whether lung fibroblasts, isolated from patients dying with acute alveolar fibrosis, use CD44 to invade a fibrin matrix. Consistent with a role for CD44 in mediating fibroblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
91
0
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 28 publications
3
91
0
3
Order By: Relevance
“…Diverse cellular functions have been attributed to CD44, including involvement in leukocyte chemotaxis and activation (23), clearance of apoptotic cells and matrix fragments (6,24), resolution of chronic inflammation (6), regulation of fibrous tissue deposition (11), and angiogenesis (25). The present study reports the first evidence that CD44 plays an essential role in infarct healing and regulates postinfarction cardiac remodeling.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Diverse cellular functions have been attributed to CD44, including involvement in leukocyte chemotaxis and activation (23), clearance of apoptotic cells and matrix fragments (6,24), resolution of chronic inflammation (6), regulation of fibrous tissue deposition (11), and angiogenesis (25). The present study reports the first evidence that CD44 plays an essential role in infarct healing and regulates postinfarction cardiac remodeling.…”
Section: Discussionmentioning
confidence: 83%
“…Second, CD44 deficiency may result in impaired fibroblast migration and invasion of the provisional matrix in the infarct. Svee et al (11) demonstrated that anti-CD44 Ab blocked fibroblast migration on the provisional matrix proteins fibronectin, fibrinogen, and HA, all important components of the healing wound (13). Third, CD44 may promote fibroblast survival by decreasing apoptosis (32).…”
Section: Role Of Cd44 In Fibrous Tissue Deposition In the Healing Infmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data indicate that CD44 may be related to fibroblast migration and pulmonary repair after injury. CD44 is the surface receptor for matrix proteins supporting cell motility, including fibronectin and hyaluronan [28], and its expression is increased in hypertrophic scar fibroblasts [29]. Interestingly, lung tissues from patients with acute alveolar fibrosis revealed CD44-expressing mesenchymal cells through newly formed fibrotic tissue and high concentrations of this surface protein were found along the motile structures (filopodia and lamellopodia) of fibroblasts [28].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence suggests that CD44 serves as a key factor in resolution of inflammation through removal of matrix breakdown products and clearance of apoptotic neutrophils [283]. CD44 also exerts fibrogenic actions mediating fibroblast migration and invasion in the wound provisional matrix [285]. Recent experiments from our laboratory tested the hypothesis that CD44 may play an essential role in infarct healing by regulating the inflammatory and fibrotic response [286].…”
Section: Clearance Of Apoptotic Neutrophils and Removal Of Matrix Debrismentioning
confidence: 99%